Love lies bleeding [videorecording (Blu-Ray)] - Glass, Rose; Tofilska, Weronika; Stewart, Kristen, 1990-; O'Brian, Katy, 1989-; Malone, Jena, 1984-; Baryshnikov, Anna, 1992-; Franco, Dave, 1985-; Harris, Ed, 1950- (A24, 2024)
Reclusive gym manager Lou falls hard for Jackie, an ambitious bodybuilder headed through town to Vegas in pursuit of her dream. But their love ignites violence, pulling them deep into the web of Lou's criminal family.